Prayer Guidance in Improving Spiritual Intelligence in Children with Physical Impairment - Sari, Widya Permata; Rahmawaty, Indira Sabet (Islamic Research, 2025)
Prayer is one of the main pillars of Islam and even serves as an identity for Muslims and their civilization. Prayer and the mosque as a place of prayer are the two leading institutions in Islam. The command to pray is obligatory for every Muslim who has reached the age of puberty, both in normal conditions and with special needs, such as even a child with a person with quadriplegia. The Special School (SLB) is one of the schools that carries out prayer guidance for children with special needs. The spiritual condition of disabled children in SLB has decreased, one of which is due to their neglect in praying. So, with this prayer, guidance is needed to improve the spiritual intelligence of children with physical impairments. The fact is that the habit of praying regularly at school and at home can raise children's awareness and motivate them to practice worship. This study aims to determine the concept of prayer guidance, prayer guidance techniques, and the results of prayer guidance in increasing spiritual intelligence in children with physical disabilities at Cileunyi State SLB, Bandung Regency. This study uses a qualitative method. The results of the study show that the concept of prayer guidance carried out there includes preparation before prayer, namely ablution, covering the genitals, determining the place and direction of prayer, and performing the prayer standing and sitting. The prayer guidance technique applied is through repetition and habituation, both individually and in groups. The results of prayer guidance show cognitive, affective, and psychomotor changes, namely: the ability to name and distinguish the time and number of prayer cycles, the ability to practice reading and prayer movements, and a change in attitude.